Information technology. Digitally recorded media for information interchange and storage. 120 mm Triple Layer (100, 0 Gbytes single sided disk and 200, 0 Gbytes double sided disk) and Quadruple Layer (128, 0 Gbytes single sided disk) BD Recordable disk. (2nd February 2021) - British Standards Institution,
No abstract available